MODERN ANALYSIS OF THE PROBLEM OF FORMING THE SYSTEM OF LONG‐TERM TABLE TENNIS PLAYERS DEVELOPMENT - Elena MOCROUSOV (Editura Universitatii Transilvania din Brasov, 2018)
In the modern sports world, preparation of athletes for the main competitions  ‐  Olympic Games or world championships  ‐  is examined through the lens of long‐term athlete development.    Specific national, political, organizational principles exist in all countries of the world;however, preparation of athletes at the same time contains many common features. First of all, this is the complexity and significant role of each of the training components in ensuring the final result: theoretical, methodological and organizational framework; material and technical conditions; concentration of financial resources, staff, and reserve training; the training process itself and competitive activity; medical and methodological support.   Conjunctive use and accounting of all components ensure success in the sports arena. Expansion of methodological framework of long‐term table tennis players development, organizational changes in the sphere of high‐performance sport, the experience of the advanced sports practice require constant consideration and improvement of the provisions underlying the rationally organized teamwork of the coach and the athlete in the training system development. The goal of this research is to form a holistic system of scientific knowledge on the basis of theoretical analysis and experimental research, to optimize the system of long‐term table tennis players'development.